2001
DOI: 10.2139/ssrn.282863
|View full text |Cite
|
Sign up to set email alerts
|

The Psychophysiology of Real-Time Financial Risk Processing

Abstract: Research support from the MIT Laboratory for Financial Engineering is gratefully acknowledged. We thank J.C. Mercier for helpful comments and discussion. The views expressed herein are those of the authors and not necessarily those of the National Bureau of Economic Research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
2
5

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(86 citation statements)
references
References 38 publications
(21 reference statements)
5
74
2
5
Order By: Relevance
“…We found that they were good at integrating disparate pieces of information, eschewed trading in volatile markets, and did not view the world as threatening their survival. These findings align with previous evidence suggesting that more experienced traders may respond in a less emotional way than those with less experience [10]. Nevertheless, other studies of professional traders have found that they are susceptible to trading biases [70][72].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found that they were good at integrating disparate pieces of information, eschewed trading in volatile markets, and did not view the world as threatening their survival. These findings align with previous evidence suggesting that more experienced traders may respond in a less emotional way than those with less experience [10]. Nevertheless, other studies of professional traders have found that they are susceptible to trading biases [70][72].…”
Section: Discussionsupporting
confidence: 91%
“…For example, Apicella et al (2008) found that levels of testosterone in saliva were associated with greater risk-taking in a laboratory investment game [9]. Field studies have also highlighted this relationship, demonstrating that when professional traders trade in volatile markets they have increased cardiovascular tone [10], and that morning testosterone levels predict professional traders' daily profits [11]. Both prenatal and circulating testosterone appear to influence the choice of a financial career and success in this field as measured by longevity [12], [13].…”
Section: Introductionmentioning
confidence: 99%
“…For example, contrary to the common belief that emotions have no place in rational financial decision-making processes, Lo and Repin [2002] present preliminary evidence that physiological variables associated with the autonomic nervous system are highly correlated with market events even for highly experienced professional securities traders. They argue that emotional responses are a significant factor in the real-time processing of financial risks, and that an important component of a professional trader's skills lies in his or her ability to channel emotion, consciously or unconsciously, in specific ways during certain market conditions.…”
Section: Adaptive Markets: the New Synthesiscontrasting
confidence: 96%
“…Recent research in the cognitive neurosciences and economics suggests an important link between rationality in decision-making and emotion (Grossberg and Gutowski [1987]; Damasio [1994]; Elster [1998]; ; Loewenstein [2000]; Peters and Slovic [2000]; and Lo and Repin [2002]), implying that the two are not antithetical, but in fact complementary.…”
Section: Adaptive Markets: the New Synthesismentioning
confidence: 99%
See 1 more Smart Citation